BIOSYNTHESIS AND CHARACTERIZATION OF GOLD NANOPARTICLES AND THEIR INTERACTION STUDY WITH METFORMIN - Dian Anggraini; Siti Suhartati; Iwan Syahjoko Saputra; Sudirman (BRIN Publishing (Penerbit BRIN), 2020)
BIOSYNTHESIS AND CHARACTERIZATION OF GOLD NANOPARTICLES AND THEIR INTERACTION STUDY WITH METFORMIN. Synthesis of gold nanoparticles successfully carried using Imperata cylindrica L leaf extract. In this study, the approach used through green synthesis method is a reaction betwen of the HAuCl4 solution (concentration variation as 3; 5; 7 x 10-4 M) with Imperata cylindrica L leaf extract. Results of UV-Vis showed of gold nanoparticles has a maximum wavelength at 530 nm with absorbance value of 1.4. Results of FTIR shows a shift the absorption peak at wavenumber of 3392 cm-1 to 3404 cm-1. PSA and PZC showed the distribution of gold nanoparticles was 48.84 nm with a charge of 20.5 mV. Gold nanoparticles has a spherical shape and an average particle size of 20 nm which can be seen from the results of the characterization using TEM. XRD showed crystalize size average of gold nanoparticles as 20.47 nm. The interaction between of gold nanoparticles with metformin can be seen in the absorbance decrease of 0.38 at a wavelength of 531 nm and the results of PSA shows an average particle size of AuNPs@metformin is 122 nm. From the characterization data can be concluded the gold nanoparticles were successfully synthesized using natural bioreductors by utilizing secondary metabolites from Imperata cylindrica L leaf extract.